Stabilization of Hypoxia-Inducible Factor-1 Alpha Augments the Therapeutic Capacity of Bone Marrow-Derived Mesenchymal Stem Cells in Experimental Pneumonia - Gupta, Naveen; Nizet, Victor (Frontiers in Medicine, 2018)
Bone marrow derived-mesenchymal stem cells (MSCs) have therapeutic effects in experimental models of lung injury. Hypoxia-inducible factor 1α (HIF-1α) is a transcriptional regulator that influences cellular metabolism, energetics and survival under hypoxic conditions. The current study investigated the effects of stabilizing HIF-1α on the therapeutic capacity of MSCs in an experimental mouse model of bacterial pneumonia. HIF-1α stabilization was achieved by the small molecule prolyl-hydroxlase inhibitor, AKB-4924 (Aerpio Therapeutics, Inc.), which blocks the pathway for HIF-1α degradation in the proteosome. In vitro, pre-treatment with AKB-4924 increased HIF-1α levels in MSCs, reduced the kinetics of their cell death when exposed to cytotoxic stimuli, and increased their antibacterial capacity. In vivo, AKB-4924 enhanced MSC therapeutic capacity in experimental pneumonia as quantified by a sustainable survival benefit, greater bacterial clearance from the lung, decreased lung injury, and reduced inflammatory indices. These results suggest that HIF-1α stabilization in MSCs, achieved ex-vivo, may represent a promising approach to augment the therapeutic benefit of these cells in severe pneumonia complicated by acute lung injury.